An Efficient Aerobic Oxidation Protocol of Aldehydes to Carboxylic Acids in Water Catalyzed by an Inorganic‐Ligand‐Supported Copper Catalyst. Issue 6 (13th February 2018) - Yu, Han; Ru, Shi; Zhai, Yongyan; Dai, Guoyong; Han, Sheng; Wei, Yongge
Abstract: A method for the aerobic oxidation of aldehydes to carboxylic acids in water by using an inorganic‐ligand‐supported copper catalyst was developed. This method was performed with the use of atmospheric oxygen as the sole oxidant under extremely mild aqueous conditions, and furthermore, a wide range of aldehydes with various functional groups were tolerated. The copper catalyst could be recycled and used in successive reactions at least six times without any appreciable degradation in performance. This method is operationally simple and avoids the use of high‐costing, toxic, air/moisture‐sensitive, and commercially unavailable organic ligands. The generality of this method gives it potential to be used on the industrial scale. Abstract : [O] what fun ! By using inorganic‐ligand‐supported copper catalyst1, various aldehydes are aerobically oxidized to carboxylic acids in water under mild and green conditions. An inorganic polymolybdate ligand is used to support the Cu 2+ ions with O2 gas as the terminal oxidant. The carboxylic acid products are obtained in excellent yields, and the use of costly, toxic, air/moisture‐sensitive, and commercially unavailable organic ligands is avoided.